ANATOMICAL STUDY OF THE RELATIONSHIP BETWEEN PLACENTAL WEIGHT, UMBILICAL CORD LENGTH, AND NEONATAL BIRTH WEIGHT - GOPAL BAGAL,; GAJANAN BHANUDAS PADMAWAR,; MANJIRI VAIBHAV GANJEWAR,; PRANITA RAMRAO GABALE, (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objective: To analyze the relationship between placental weight and umbilical cord length with neonatal birth weight in term singleton pregnancies and to identify whether placental and cord parameters can serve as a predictor of fetal growth outcomes. Methods: This hospital-based, cross-sectional study was conducted from January to December 2024 in the Department of Obstetrics and Gynecology of a tertiary care center. A total of 60 term singleton pregnancies (37–42 weeks) were included based on predefined inclusion and exclusion criteria. Immediately post-delivery, neonatal weight was recorded using a digital scale. Umbilical cord length was measured from placental insertion to the neonatal end, and the trimmed placenta was weighed with an electronic balance. Data were statistically analyzed using the Statistical Package for the Social Sciences v23.0. Pearson was applied to determine relationships among placental weight, cord length, and birth weight. Results: The mean placental weight was 588.8 g. The mean umbilical cord length was 41.12 cm, and the mean neonatal birth weight was 2963.83 g. There was a strong positive relationship between placental weight and birth weight as indicated by a Pearson correlation coefficient (r) of 0.9983. This correlation was statistically highly significant, with a p<0.001. The mean umbilical cord length in the studied cases was 41.117 cm, whereas the mean birth weight was 2963.83 g. The association was not statistically significant (p=0.1305). Conclusion: Placental weight demonstrates a significant positive association with neonatal birth weight. However, umbilical cord length lacks statistical significance for the prediction of birth weight. Post-delivery placental evaluation may aid retrospective assessment of fetal well-being and inform perinatal risk stratification.